Identifying gaps between perceived and actual intakes in Finnish adults: self-assessment of macronutrient intakes in relation to nutrition recommendations is challenging - Sari Bäck; Tiina Pellinen; Essi Päivärinta; Petra Rautio; Antti Isokangas; Maijaliisa Erkkola; Anne-Maria Pajari (Food & Nutrition Research)
Background: Population adherence to nutrition recommendations measured by dietary surveys is well known, but people’s perceptions in adherence to nutrition recommendations are less explored. For macronutrients, nutrition recommendations suggest broad intake ranges. Objective: To study individuals’ perceptions of their macronutrient intakes compared to the Nordic Nutrition Recommendations and discrepancies between perceived and actual macronutrient intakes. Design: The ScenoProt trial investigated nutritional and health effects of replacing animal-source proteins with plant-source proteins in Finnish adults (n = 102, 78% women, mean age 47 years). This cross-sectional sub-study utilized data collected at the baseline of the trial. Participants’ perceptions of intakes and sources of carbohydrates, fibers, fats, and proteins were collected by a questionnaire developed for the study. Actual macronutrient intakes and sources were assessed with 4-day food records. Logistic regression analysis was used to examine associations between sociodemographic factors and the capacity to self-assess macronutrient intakes relative to the nutrition recommendations. Results: Discrepancies were found in relative proportions of three categories, below/according to/above the recommendation, between perceived and actual macronutrient intakes regarding the nutrition recommendations. Participants rated themselves rather according to or above than below the recommendation. The most distinct gap was discovered between perceived and actual carbohydrate intakes, for example, proportions of participants being below the recommendation: 8% measured as perceived intake; 70% measured as actual mean intake. Gaps were also observed for fat and protein. Cereals were one of the most common protein sources but only 8% of the participants named them. No associations emerged between age, gender, or education (46% with a master’s degree or higher) and the capacity to self-assess macronutrient intakes. Discussion & conclusions: Our study suggests that self-assessment of macronutrient intakes is challenging. Misperceptions can be obstacles in shifting to healthier and more sustainable diets. Interpretation of nutrition recommendations to the public could still be improved.